A STUDY OF SOME NON GENETIC FACTORS AND GENETIC PARAMETERS OF BODY WEIGHTS, DIMENSIONS AND FAT TAIL DIMENSIONS OF AWASSI SHEEP - Faris Y.Abdul-Rahman (Mesopotamia Journal of Agriculture)
The study included 276 Awassi lambs born during the lambing season 2007 and 2008 and were maintained at College of Agriculture and Forestry Station, University of Mosul, and Animal Breeding Station, Mosul Al-Rashedia. The studied traits were : birth weight , body weight , body and fat tail dimensions namely (body length , heart girth , height at shoulder , height at hip , depth at shoulder , depth at hip , width at shoulder , width at hip , fat tail length , fat tail width and fat tail circumference) at weaning (4) , 6 and 8 months of ages . The effects of flock, year of lambing, age of dam, type of birth and sex of lamb on the above traits were investigated. The flock affect significantly (p<0.01) all studied traits at different ages. Year had a significant influence (p<0.01) on weight at 6 and 8 months of age and most body dimensions and fat tailed dimensions at different ages. No significant effect of age of dam was found on birth and weaning weight, whereas its effect was significant (p<0.05) on weight at 6 and 8 months of age. The effect of type of birth was significant on all body weights and dimensions from birth till 8 months of age. Sex of lamb had a significant influence on weight at weaning , 6 and 8 months of ages and on most body and fat tail dimensions , while its effect was not significant on birth weight .